2022
DOI: 10.1096/fj.202101626rr
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine attenuates renal ischemia–reperfusion injury through activating PI3K/Akt‐eNOS signaling via α2 adrenoreceptors in renal microvascular endothelial cells

Abstract: Renal microvascular endothelial cells (RMECs), which are closely related to regulation of vascular reactivity and modulation of inflammation, play a crucial role in the process of renal ischemia and reperfusion (I/R) injury. Previous studies have reported the protective effects of dexmedetomidine (DEX) against renal I/R injury, but little is known about the role of DEX on RMECs. This study aimed to investigate whether DEX alleviated renal I/R injury via acting on the RMECs.Mice underwent bilateral renal artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Third, dexmedetomidine induces renal vasodilatation by regulating endothelial nitric oxide, which increases renal blood flow, glomerular filtration, and urine output [53,54]. Fourth, recent experimental studies showed that the attenuation of renal I/R injury by dexmedetomidine involves inhibition of ferroptosis, activation of the cholinergic anti-inflammatory pathway, and regulation of renal microvascular endothelial cells [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Third, dexmedetomidine induces renal vasodilatation by regulating endothelial nitric oxide, which increases renal blood flow, glomerular filtration, and urine output [53,54]. Fourth, recent experimental studies showed that the attenuation of renal I/R injury by dexmedetomidine involves inhibition of ferroptosis, activation of the cholinergic anti-inflammatory pathway, and regulation of renal microvascular endothelial cells [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of metabolic reprogramming, this study elucidates the important role of eNOS in renal injury, providing us with new ideas for further prevention and treatment of hypertensive kidney injury from the perspective of metabolic reprogramming. Multiple studies [ [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] ] have found that eNOS is closely related to hypertension, kidney injury, etc. eNOS can make an decrease in PKM2, which is an important mediator for catalyzing glycolysis and increasing the conversion of phosphoenolpyruvate (PEP) to pyruvate.…”
Section: Disscussionmentioning
confidence: 99%